Factors Influencing Customer Satisfaction in Butwal Sub-Metropolitan City Gyms - Gurung, Ganesh (Devkota Journal of Interdisciplinary Studies, 2023)
This research examined the variables that influence individuals’ satisfaction levels at fitness facilities, encompassing factors such as cost, proximity, advertising efficacy, and equipment quality. The objective was to assist gym owners in improving their services and ensuring the satisfaction of their clientele. The study revealed that while the presence of high-quality gym equipment is deemed crucial, its impact on customer satisfaction was found to be negligible. Conversely, factors such as location, advertising, and affordability were identified as significant determinants of customer satisfaction. The proposition posits that in order to enhance customer satisfaction, proprietors of fitness establishments should prioritize the facilitation of convenient access, the establishment of reasonable pricing, and the implementation of effective promotional strategies. In a highly competitive market, identifying and effectively resolving these concerns can lead to increased customer satisfaction and overall business prosperity for the health center.